SCORE MODEL AND RISK LITIGATION: INVESTIGATING THE IMPACT OF FRAUD IN REPORT CORPORATE FINANCE - Supriatiningsih; Hidayat Darwis; Pandaya; Ridwan Saleh; Ramayuli (International Journal Management and Economic, 2024)
Study This testing the Score model against fraud reports financial impact on risk​ litigation company. The independent variable is SCORE (stimulus, capability, opportunity, rationalization and ego) while the fraud report finance as an intervening variable and risk litigation is the dependent variable. In research This population used​ is company sector mining companies registered in Indonesia with total of 30 companies. Research data This is secondary data in the form of report annual companies that can accessed on the Indonesia Stock Exchange (www.idx.co.id). The data analysis method uses the analysis model regression multiple. Analysis This use calculation statistics Eviews 12. Testing using: statistics descriptive. t-statistic test and hypothesis test Stability finance, Nature of industry and amount audit committee does not own influence on fraud report finance. The proportion of independent commissioners and political connections have a significant effect on financial report fraud. Fraud report finance does not influential to litigation company.